Peran Mahasiswa Dalam Mendukung Tata Kelola Keuangan Daerah: Studi Literatur - Firdaus Ro`mah; Jumadi; Muhammad Budi Utama (Journal of Public Sector Financial Management, 2026)
This study aims to identify and analyze the role of students in supporting regional financial management, particularly in promoting transparency, accountability, and public participation. This study uses a descriptive qualitative method with a literature review approach. Data were obtained from various scientific articles and academic publications discussing regional financial management, transparency, accountability, and the role of students. The data obtained was then analyzed thematically to obtain a complete picture. The results of the study show that students have an important role as agents of education to the community, partners of local governments in academic and community service activities, and as social supervisors of regional financial management. However, the role of students is still not optimal because their involvement is temporary and not integrated in a sustainable manner. This study is expected to broaden understanding of the role of students in regional financial management and serve as a consideration for local governments and universities in building more sustainable cooperation.